2018
DOI: 10.1097/wco.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic inflammatory demyelinating polyradiculopathy

Abstract: Several studies evaluating the best strategy to provide maintenance IVIg treatment in CIDP are in progress. SCIg were shown to be an alternative to IVIg for maintenance treatment while their efficacy as initial therapy should be further addressed. New outcome measures have been shown to be effective in detecting treatment response in clinical trials, but their use in clinical practice remains uncertain. Similarly unsettled is the role of nerve imaging techniques as biomarker in CIDP. The discovery of antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
(43 reference statements)
0
7
0
1
Order By: Relevance
“…Second, a larger group of patients could have added significant details on LT‐SCIg therapy; however, this was a homogeneous group of Ig‐responder patients and ideal for analysis of both clinical and neurophysiological response to SCIg treatment. Third, despite the recent suggestion of a novel regimen of SCIg administration (bolus dose, a concentrated dose every week) for CIDP maintenance therapy or the intermittent reduction of the weekly SCIg dose to test for remission, our treatment was continued for 48 months without dose changes because we had previously observed persistent alterations of nerve conduction at 24 months, but also progressive clinical improvement, reduced disability, and improved QoL.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, a larger group of patients could have added significant details on LT‐SCIg therapy; however, this was a homogeneous group of Ig‐responder patients and ideal for analysis of both clinical and neurophysiological response to SCIg treatment. Third, despite the recent suggestion of a novel regimen of SCIg administration (bolus dose, a concentrated dose every week) for CIDP maintenance therapy or the intermittent reduction of the weekly SCIg dose to test for remission, our treatment was continued for 48 months without dose changes because we had previously observed persistent alterations of nerve conduction at 24 months, but also progressive clinical improvement, reduced disability, and improved QoL.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, dCMAP amplitude significantly increased at 48 months com- 32 for CIDP maintenance therapy or the intermittent reduction of the weekly SCIg dose to test for remission, 33 our treatment was continued for 48 months without dose changes because we had previously observed persistent alterations of nerve conduction at 24 months, 11…”
Section: Clinical-neurophysiological Correlation Analysismentioning
confidence: 97%
“…[1][2][3][4][5][6][7] There is still no consensus on how many and which outcome measures should be used in routine clinical practice. 8 Moreover, it is still unclear which minimum clinical important difference (MCID) cutoff values are appropriate for individual patient assessment. 8 Although different MCID thresholds have been proposed for various outcome measures, with positive results in randomized clinical trials, it is not clear whether they are appropriate in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, it is still unclear which minimum clinical important difference (MCID) cutoff values are appropriate for individual patient assessment. 8 Although different MCID thresholds have been proposed for various outcome measures, with positive results in randomized clinical trials, it is not clear whether they are appropriate in clinical practice. For instance, in the ICE study, almost 26% of the patients treated with placebo showed improvement in their grip strength (GS) greater than the proposed MCID cutoff value of 8 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…The current first-line treatment of CIDP includes intravenous immunoglobulin (IVIG), corticosteroids, and plasma exchange (PE) ( 1 , 2 , 27 ), and now, subcutaneous immunoglobulin (SCIG) has been gradually used for the maintenance treatment of CIDP patients who respond well to IVIG due to its similar efficacy and convenience, reducing infusion-related side effects ( 28 , 29 ). However, more than 20% of patients do not respond to standard therapies, other biological agents, or immunosuppressive agents such as azathioprine, cyclophosphamide, ciclosporin, mycophenolate mofetil, and rituximab, which can be used as a secondary therapy when the first-line treatment was not effective or tolerated ( 1 , 2 , 10 , 12 ).…”
Section: Overview Of Cidpmentioning
confidence: 99%